KONSEP PENDIDIKAN YAYASAN PERGURUAN TAMAN SISWA KOTA PAGARALAM - Yatim Kasianto (IAIN Bengkulu, 2017)
Islamic Education undergone many developments. Cultural differences among people make new sciences that needs solving swatch and solutions in the development of Islamic education. Education is the main pillar to keep pace with the development of science and technology. We are not only in demand proficient in science and technology alone but also need to be balanced with spiritual values in order to avoid gaps in personality. System in education conceptual and forming an interrelated components between one another among them are the curriculum, principles, objectives, and infrastructure that support so that the learning process so that the aut put at yield experiencing mental improvement that will manifest in good acts for himself or in public life. The research was conducted using qualitative descriptive method means to describe the actual state of the object on conscientious and of course to get the materials and the data the researchers used, observation and interviews with various stakeholders am o ng Community Leaders, Religious Leaders, the Heir who accountable, school principals, teachers, Alumni Pagaralam City Government especially those of the head of the Department of Education, Ministry of Religious Affairs in addition, researchers also refer to the documents / archive heritage of antiquity and then documented. System and the concept of Unity College Foundation Student Park using the pattern of education system Among the method of educating the spirit of kinship based on the independence and the nature of nature as instructed founder Ki Hajar Dewantara. In Pagaralam since the establishment of the University Student Park has undergone many ups and downs quantity of students from the first period to the present, while the limiting factor is caused partly because the facilities and teaching aids as well as educators and the media learned that only rely on the government so that admintrated school ordered but not yet inventoried continuously. Conditions amid public schools also make the inevitable constraints then the need for the parties concerned to limit the admission of students to the balance went into private school